2019
DOI: 10.1042/bsr20190104
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value and safety of color doppler ultrasound-guided transthoracic core needle biopsy of thoracic disease

Abstract: Objective: The aim of the present study was to explore the diagnostic value and safety of color Doppler ultrasound (US)-guided transthoracic core needle biopsy (CNB) of peripheral lung, chest wall and mediastinal lesions using automated biopsy guns. Materials and methods: We analyzed clinical and image data, histopathologic and microbiologic details and complications from 121 patients with peripheral lung, chest wall and mediastinal lesions who underwent color Doppler US-guided transthoracic CNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…Three patients required chest tube insertion, and the percentage of chest tube insertion was 1.1 % in the present study, which is within the reported range of 0e2%. 3,11,12,22,23 In the present study, compared with supine position, significantly more complications were seen in patients managed with lateral position when using 16-G core needles (p¼0.029, OR ¼ 3.407). In other words, the lateral position increased the incidence of overall complications approximately 3.4-fold compared with the supine position.…”
Section: Discussionmentioning
confidence: 47%
“…Three patients required chest tube insertion, and the percentage of chest tube insertion was 1.1 % in the present study, which is within the reported range of 0e2%. 3,11,12,22,23 In the present study, compared with supine position, significantly more complications were seen in patients managed with lateral position when using 16-G core needles (p¼0.029, OR ¼ 3.407). In other words, the lateral position increased the incidence of overall complications approximately 3.4-fold compared with the supine position.…”
Section: Discussionmentioning
confidence: 47%
“…Lesion movement is with breathing [32]. Therefore, before performing the procedure, the size of the lesion needs to be assessed and the appropriate guidance modality selected to improve the pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic pneumothorax is a common complication resulting from many pulmonary interventions. The reported incidence of iatrogenic pneumothorax is as follows: 0.8-1.4% in patients undergoing radial endobronchial ultrasound-guided transbronchial lung biopsy, approximately 2-6% among patients undergoing thoracentesis, 0.6-9% in patients undergoing echo-guided biopsy, and as high as 42% among patients undergoing CT (computed tomography)-guided lung biopsy [1][2][3][4][5][6][7][8] . The British Thoracic Society guidelines in 2010 suggested that observation alone is adequate for majority of the cases of iatrogenic pneumothorax and that, if intervention is required, simple aspiration be considered 9,10 .…”
Section: Introductionmentioning
confidence: 99%